Felix Berezin : the life and death of the mastermind of supermathematics - Shifman, Mikhail A. (World Scientific, 2007)
Felix Berezin was an outstanding Soviet mathematician who in the 1960s and 70s was the driving force behind the emergence of the branch of mathematics now known as supermathematics. The integral over the anticommuting Grassmann variables that he introduced in the 1960s laid the foundation for the path integral formulation of quantum field theory with fermions, the heart of modern supersymmetric field theories and superstrings. The Berezin integral is named for him, as is the closely related construction of the Berezinian, which may be regarded as the superanalog of the determinant. This book f.